Evaluation of neuromotor development by means of the Harris Infant Neuromotor Test - Márcia Maria Coelho Oliveira Lopes; Maria Vera Lúcia Moreira Leitão Cardoso (SciELO, 2014)
Objective: To investigate the neuromotor development of at-risk children between three and 12 months of life, administering the Brazilian version of the Harris Infant Neuromotor Test (HINT).Method: A longitudinal study, with 78 children and 76 parents/guardians discharged from a neonatal intensive care unit in Fortaleza-CE/Brazil. Two instruments were administered: HINT and a socioeconomic questionnaire, between July/2009 to August/2010. Data from 55 preterm and 23 term children were analyzed. Results: The final mean scores ranged from 14.6 to 25.2 and from 11.2 to 24.7, for preterm and term, respectively, showing that 91% of children demonstrated good neuromotor performance; seven premature infants showed alterations which led to the referral of three children to a specialized clinic for examination and diagnostics.Conclusion: The test allowed nurses to assess infant development, identify deviations early, and plan interventions.